2016
DOI: 10.1155/2016/2961954
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Protects H9C2 Cardiomyocytes from High-Glucose and Hypoxia/Reoxygenation Injury via Inhibition of Reactive Oxygen Species Generation and Inflammatory Responses: Role of AMPK and JNK

Abstract: Metformin is a first-line drug for the management of type 2 diabetes. Recent studies suggested cardioprotective effects of metformin against ischemia/reperfusion injury. However, it remains elusive whether metformin provides direct protection against hypoxia/reoxygenation (H/R) injury in cardiomyocytes under normal or hyperglycemic conditions. This study in H9C2 rat cardiomyoblasts was designed to determine cell viability under H/R and high-glucose (HG, 33 mM) conditions and the effects of cotreatment with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 34 publications
(35 reference statements)
4
43
0
2
Order By: Relevance
“…Clinical trials and registries have consistently shown that metformin does not increase cardiovascular morbidity and mortality of diabetic patients; in fact, a favourable effect of metformin on diabetes-related cardiovascular risk has been reported [5]. Consistently, most experimental studies have demonstrated that metformin prevents ischemic cardiac damage, this protection being ascribed to various pathways, not necessarily downstream of the reduction in complex I activity, such as activation of AMPK and phosphoinositide 3-kinase/ AKT, enhanced intramyocardial availability of adenosine, blunting of oxidative stress, and inhibition of mitochondrial permeability transition pore opening [24,31]. By contrast, therapy with glibenclamide has been associated with negative cardiovascular outcomes in epidemiological analysis [2,3] and glibenclamide has been shown to worsen ischemic injury of cardiomyocytes in cell and animal models [31].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 77%
See 2 more Smart Citations
“…Clinical trials and registries have consistently shown that metformin does not increase cardiovascular morbidity and mortality of diabetic patients; in fact, a favourable effect of metformin on diabetes-related cardiovascular risk has been reported [5]. Consistently, most experimental studies have demonstrated that metformin prevents ischemic cardiac damage, this protection being ascribed to various pathways, not necessarily downstream of the reduction in complex I activity, such as activation of AMPK and phosphoinositide 3-kinase/ AKT, enhanced intramyocardial availability of adenosine, blunting of oxidative stress, and inhibition of mitochondrial permeability transition pore opening [24,31]. By contrast, therapy with glibenclamide has been associated with negative cardiovascular outcomes in epidemiological analysis [2,3] and glibenclamide has been shown to worsen ischemic injury of cardiomyocytes in cell and animal models [31].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 77%
“…Metformin and glibenclamide are very different molecules with different mechanism of action. Similarly to metformin [23,24] glibenclamide increases AMPK phosphorylation and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The effectiveness of metformin as an antihyperglycemic agent is based on its ability to suppress gluconeogenesis in the liver. 5,8 In addition, metformin has been identified as an activator of the AMP-activated protein kinase (AMPK) pathway in numerous cell types including hepatocytes, 9 endothelial cells, 10 cardiomyocytes, 11 cancer cells, 12 and adipose tissue. 13 In addition to its use as an antihyperglycemic agent, one beneficial effect from metformin is mild weight loss.…”
mentioning
confidence: 99%
“…AMPK activation suppresses protein synthesis in heart tissue and post-MI hypertrophy (18). Hu et al have shown, for the first time, that metformin could protect cardiomyocytes against high-glucose (HG) and hypoxia/reoxygenation (H/R) injury by suppressing Jun NH(2)-terminal kinase (JNK) activation and raising AMPK activation (19). Metformin also impresses gastrointestinal tract by reducing inflammation.…”
Section: Anti-inflammatory Mechanism Of Metforminmentioning
confidence: 99%